Deep learning predicts epidermal growth factor receptor mutation subtypes in lung adenocarcinoma. Issue 12 (7th November 2021) - Song, Jiangdian; Ding, Changwei; Huang, Qinlai; Luo, Ting; Xu, Xiaoman; Chen, Zongjian; Li, Shu
Abstract: Purpose: This study aimed to explore the predictive ability of deep learning (DL) for the common epidermal growth factor receptor ( EGFR ) mutation subtypes in patients with lung adenocarcinoma. Methods: A total of 665 patients with lung adenocarcinoma (528/137) were recruited from two different institutions. In the training set, an 18‐layer convolutional neural network (CNN) and fivefold cross‐validation strategy were used to establish a CNN model. Subsequently, an independent external validation cohort from the other institution was used to evaluate the predictive efficacy of the CNN model. Grad‐weighted class activation mapping (Grad‐CAM) technology was used for the visual interpretation of the CNN model. In addition, this study also compared the prediction abilities of the radiomics and CNN models. Receiver operating characteristic (ROC) curves, accuracy and precision values, and recall and F1‐score were used to evaluate the effectiveness of the CNN model and compare its performance with that of the radiomics model. Results: In the validation set, the micro‐ and macroaverage values of the area under the ROC curve of the CNN model to identify the three EGFR subtypes were 0.78 and 0.79, respectively. All evaluation indicators of the CNN model were better than those of the radiomics model. Conclusions: Our study confirmed the potential of DL for predicting the EGFR mutation status in lung adenocarcinoma. The imaging phenotypes of the three mutation subtypes were found to be different, which can provide a basis for choosing more accurate and personalized treatment in patients with lung adenocarcinoma.